Evaluation of bond strength and adhesive remnant index of different lingual retainers in human incisor teeth - Cherukupalli Sowmya; Puthamakula Brahmini; Manjula K Thimmaiah; Radhika Thakkar; Sandeep Kumar; Moode K Naik (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aimed to evaluate and compare the bond strengths of four different lingual retainers and assess the adhesive remnant index (ARI) to determine their effectiveness in orthodontic retention. Methodology: Eighty human incisor teeth were divided into four groups, with each group bonded using a different retainer: Group 1 (E-Glass retainer), Group 2 (0.017" Co-axial stainless steel wire), Group 3 (Splint C.T. fiber mesh), and Group 4 (0.010" stainless steel ligature wire). Bond strength was measured using a universal testing machine, and ARI scores were recorded to assess bond failure types. Results: Group 1 (E-Glass retainer) demonstrated the highest bond strength, followed by Group 3 (Splint C.T. fiber mesh), Group 2 (Co-axial stainless steel wire), and Group 4 (stainless steel ligature wire). Cohesive bond failures were observed in most groups, except for the co-axial stainless steel wire group, which exhibited adhesive failures. Conclusion: E-Glass fiber-reinforced retainers showed the highest bond strength, making them a promising alternative to conventional stainless steel wires for orthodontic retention, especially in patients with esthetic concerns or nickel hypersensitivity. Stainless steel retainer groups exhibited lower bond strengths, and cohesive bond failures were prevalent. Further research is needed to validate these findings in clinical settings and evaluate the long-term effectiveness of different lingual retainers.